The impact of COVID-19 on health financing in Kenya. - Angela Kairu; Stacey Orangi; Boniface Mbuthia; Brian Arwah; Fatuma Guleid; Janet Keru; Ileana Vilcu; Anne Musuva; Nirmala Ravishankar; Edwine Barasa (Public Library of Science (PLoS), 2023)
Sudden shocks to health systems, such as the COVID-19 pandemic may disrupt health system functions. Health system functions may also influence the health system's ability to deliver in the face of sudden shocks such as the COVID-19 pandemic. We examined the impact of COVID-19 on the health financing function in Kenya, and how specific health financing arrangements influenced the health systems capacity to deliver services during the COVID-19 pandemic.We conducted a cross-sectional study in three purposively selected counties in Kenya using a qualitative approach. We collected data using in-depth interviews (n = 56) and relevant document reviews. We interviewed national level health financing stakeholders, county department of health managers, health facility managers and COVID-19 healthcare workers. We analysed data using a framework approach. Purchasing arrangements: COVID-19 services were partially subsidized by the national government, exposing individuals to out-of-pocket costs given the high costs of these services. The National Health Insurance Fund (NHIF) adapted its enhanced scheme's benefit package targeting formal sector groups to include COVID-19 services but did not make any adaptations to its general scheme targeting the less well-off in society. This had potential equity implications. Public Finance Management (PFM) systems: Nationally, PFM processes were adaptable and partly flexible allowing shorter timelines for budget and procurement processes. At county level, PFM systems were partially flexible with some resource reallocation but maintained centralized purchasing arrangements. The flow of funds to counties and health facilities was delayed and the procurement processes were lengthy. Reproductive and child health services: Domestic and donor funds were reallocated towards the pandemic response resulting in postponement of program activities and affected family planning service delivery. Universal Health Coverage (UHC) plans: Prioritization of UHC related activities was negatively impacted due the shift of focus to the pandemic response. Contrarily the strategic investments in the health sector were found to be a beneficial approach in strengthening the health system. Strengthening health systems to improve their resilience to cope with public health emergencies requires substantial investment of financial and non-financial resources. Health financing arrangements are integral in determining the extent of adaptability, flexibility, and responsiveness of health system to COVID-19 and future pandemics.